If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(a + 3) + y(a + 3) = 0 Reorder the terms: X(3 + a) + y(a + 3) = 0 (3 * X + a * X) + y(a + 3) = 0 (3X + aX) + y(a + 3) = 0 Reorder the terms: 3X + aX + y(3 + a) = 0 3X + aX + (3 * y + a * y) = 0 Reorder the terms: 3X + aX + (ay + 3y) = 0 3X + aX + (ay + 3y) = 0 Solving 3X + aX + ay + 3y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1ay' to each side of the equation. 3X + aX + ay + -1ay + 3y = 0 + -1ay Combine like terms: ay + -1ay = 0 3X + aX + 0 + 3y = 0 + -1ay 3X + aX + 3y = 0 + -1ay Remove the zero: 3X + aX + 3y = -1ay Add '-3y' to each side of the equation. 3X + aX + 3y + -3y = -1ay + -3y Combine like terms: 3y + -3y = 0 3X + aX + 0 = -1ay + -3y 3X + aX = -1ay + -3y Reorder the terms: 3X + aX + ay + 3y = -1ay + ay + -3y + 3y Combine like terms: -1ay + ay = 0 3X + aX + ay + 3y = 0 + -3y + 3y 3X + aX + ay + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 3X + aX + ay + 3y = 0 The solution to this equation could not be determined.
| -3(8-11j)=-5(12-6j) | | -3=3x-6x+18 | | 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 |